Rainbow Fish and the whale - Pfister, Marcus; James, J. Alison (New York : North-South, 2011)
A big blue whale comes to live near the reef creating a misunderstanding between him and Rainbow Fish and his friends that leaves everyone very unhappy and hungry.
"Tuff books"--Cover.
Previously published: Rainbow Fish and the big blue whale.
Translation of: Der Regenbogenfisch schliesst Frieden.
2.2
Preschool
Preschool
Keywords: Fighting (Psychology) -- Juvenile fiction; Fishes -- Juvenile fiction; Whales -- Juvenile fiction; Fighting (Psychology) -- Fiction; Fishes -- Fiction; Whales -- Fiction; Communication -- Fiction; Fishes -- Fiction; Whales -- Fiction; Picture books for children